Impact of Psychological Empowerment, Self-Efficacy and Workaholism on Organizational Citizenship Behavior among Teachers - Jadoon, Noor Us Saba; Sohail, Rahma; Khalil, Saira (Annals of Human and Social Sciences, 2023)
This study investigates the impact of psychological empowerment, self-efficacy, and workaholism on organizational citizenship behavior (OCB) among 214 school teachers in government and private schools in Pakistan. Utilizing the Organizational Citizenship Behavior Scale, Psychological Empowerment Questionnaire, Teacher’s Self-Efficacy Scale, and Dutch Work Addiction Scale. The results indicate positive predictions of OCB by psychological empowerment, self-efficacy, and workaholism. The findings revealed non-significant differences in self-efficacy and organizational citizenship behavior between teachers in government and private schools. However, private school teachers reported higher levels of psychological empowerment and workaholism compared to their counterparts in government schools. In conclusion, fostering a supportive and empowering environment is vital for enhancing teachers’ engagement in OCB. Practical implications involve strategies promoting teacher empowerment, self-efficacy, and work-life balance for positive workplace behaviors and improved education quality. This study underscores the role of psychological factors and workaholism in predicting teachers’ engagement in OCB.